POLITIK HUKUM ATAS PENCEGAHAN TINDAK PIDANA KORUPSI DI BIDANG KONSTRUKSI INDONESIA - I Made Sukartha (Jurnal HUKUM BISNIS, 2023)
Currently what is being highlighted by the Indonesian people is law enforcement against perpetrators of corruption, because many still doubt law enforcement. The community considers that law enforcers are still indicated to be influenced by power, whether in a person's position or status. Therefore, cases of corruption are still common today, and efforts to enforce the law have not had a deterrent effect on society, and have not had a significant effect on reducing corruption. Corruption practices in the construction sector are still common in Indonesia. Even though regarding criminal acts of corruption there is already a Corruption Law, namely Number: 31 of 1999 concerning Eradication of Corruption Crimes, which has been amended by Law Number: 20 of 2001. In this study, normative juridical research was used, with analytical descriptive specifications. The approaches used include statutory approach, conceptual approach, and historical approach. Efforts to deal with corruption through the means of criminal law have not been maximized, so policies for dealing with criminal acts of corruption must also be sought and directed at efforts to prevent and eliminate factors that have the potential to cause corruption. One of the efforts to overcome and prevent criminal acts of corruption, must start enforcing the law by following the example of other countries which apply the maximum penalty, namely life imprisonment or death penalty for perpetrators of corruption, which are truly proven and carried out in a state experiencing an economic crisis. or done repeatedly. . Keywords: Corruption in Construction Sector, Law Enforcement, Prevention of Corruption, Legal Politics